PENERAPAN PEMBERDAYAAN PETANI DENGAN TEKNOLOGI AGRITECH PADA KELOMPOK TANI UNTUK MENDUKUNG KETAHANAN PANGAN WILAYAH RAWAN BENCANA - Hasibuan, Annalisa Sonaria; Andi Supriadi Chan; Rezha Destiadi (Fakultas Ilmu Komputer, 2025)
Inadequate technology during the planting phase, particularly in identifying pests or diseases, swiftly emerges as the primary impediment to enhancing crop yields over extensive areas. The insufficient comprehension and knowledge of the Lingga village community regarding the significance of agritech technologies contribute to the low wellbeing of farmers and agricultural labourers. This issue affects the harvest production index, diminishes potential regional economic contributions, and undermines food security initiatives, particularly in disaster-prone regions. This activity's knowledge and technology transfer concept is delineated into three phases. The initial phase involves the preparation of activities, followed by the implementation of coaching activities and the evaluation of those activities. Agritech utilising drones for terrestrial sampling and photogrammetry. This method detects pest proliferation on agricultural land by mapping afflicted areas through condition maps generated from drone imagery and imaging. This device is engineered for optimal coverage to access agricultural areas impacted by pest proliferation and to capture photographs of the farmland. The employed technology includes a camera component that autonomously captures images based on input from the drone, subsequently generating photographs with GPS logs to provide coordinates for processing.